2012
DOI: 10.1002/14651858.cd001894.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Assisted hatching on assisted conception (in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI))

Abstract: Assisted hatching on assisted conception (in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 84 publications
1
83
1
Order By: Relevance
“…While there have been multiple reports comparing ART outcomes in cycles with and without AH, most have defined poor prognosis as prior failed cycles or based on maternal age rather than looking specifically at FSH concentration. Many such studies support a role for AH in improving clinical pregnancy rates in women who are at least 38 years old or who have had unsuccessful prior ART cycles; several studies have also demonstrated improvements in ongoing/live birth rates in these subpopulations (1922, 36). In contrast, Assemi et al published a study more analogous to ours in its comparison of 154 initial ART cycles all with FSH >=10 IU/L according to whether AH was performed.…”
Section: Discussionmentioning
confidence: 88%
“…While there have been multiple reports comparing ART outcomes in cycles with and without AH, most have defined poor prognosis as prior failed cycles or based on maternal age rather than looking specifically at FSH concentration. Many such studies support a role for AH in improving clinical pregnancy rates in women who are at least 38 years old or who have had unsuccessful prior ART cycles; several studies have also demonstrated improvements in ongoing/live birth rates in these subpopulations (1922, 36). In contrast, Assemi et al published a study more analogous to ours in its comparison of 154 initial ART cycles all with FSH >=10 IU/L according to whether AH was performed.…”
Section: Discussionmentioning
confidence: 88%
“…We conducted this study due to the paucity of data indicating the role of AH on the outcome in cases without known poor prognosis with their first fresh cycles (21).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed higher implantation rate in group with blastocyst stage embryo transfer and partial assisted hatching in this group resulted in favorable outcome (20). However, there is still no clear evidence indicating the role of AH on the outcome of cases without known poor prognosis with their first fresh cycles (21).…”
Section: Introductionmentioning
confidence: 92%
“…Yet, the effectiveness of AH to improve the outcome of fresh and frozen IVF/ICSI-ET cycles remains controversial (Ng et al, 2005;Ge et al, 2008;Lan et al, 2009;Carney et al, 2012;Razi et al, 2013;Wan et al, 2014).…”
Section: Assisted Hatching In Frozen Cyclesmentioning
confidence: 99%